Histology of the spermateca and stored sperm of Tenuisvalvae notata (Coleoptera: Coccinellidae). (13th May 2018) - Túler, Amanda C.; Silva‐Torres, Christian S. A.; Teixeira, Valéria W.; Teixeira, Alvaro A. C.; Guedes, Carolina A.; D'Assunção, Carolline G.; Brayner, Fábio A.; Alves, Luiz C.
Abstract: The predatory ladybird beetle Tenuisvalvae notata (Coleoptera: Coccinellidae) (Mulsant) is a polygamous species and its morphology, as well as the storage capacity of seminal fluid in the spermatheca, may affect its reproductive performance. Thus, the present study evaluates the spermatheca morphology of virgin and mated T. notata females using light and scanning microscopy. The results show that the spermatheca of T. notata is kidney shaped and consists only of the receptacle and spermathecal duct, being morphologically similar in virgin and mated females. There is no secretion in the spermathecae of virgin females and, in mated females, only once it was not possible to observe the presence of spermatozoa. By contrast, females mate multiple times it is possible to observe spermatozoa in the lumen of the spermatheca surrounding the secreted material. Polygamy in T. notata might be related to the maintenance of viable spermatozoa in the spermatheca, in which case the female would prefer to copulate more times during its adult life than to store spermatozoa for a longer period of time. Abstract : The spermatheca of Tenuisvalvae notata is simple, rhiniform in shape and consists only of the receptacle and spermatic duct. Spermatozoid cells are not observed in the lumen of the spermatheca of once‐mated females, although they are found in the spermatheca of multiple mated ones. There is no difference in the morphology of the spermatheca of virgin, once‐mated and multiple‐mated females.